DOI: 10.11606/d.11.2013.tde-11092013-151731
|View full text |Cite
|
Sign up to set email alerts
|

Descrição macroscópica e microscópica da madeira aplicada na identificação das principais espécies comercializadas no estado de São Paulo - Programas "São Paulo Amigo da Amazônia" e "Cadmadeira"

Abstract: Macroscopic and microscopic description of wood applied in the identification of the main commercial species in the State of São Paulo-Programs "São Paulo Amigo da Amazonia" and "Cadmadeira" The exploitation of the wood, especially in the Amazon region, has increased in the last decades. It is estimated that 24 million m³ of wood in trunk forms are being extracted from the Amazon forest, where approximately 15% are bought by the Paulista's market (the consumers from Sao Paulo). This fact makes Sao Paulo the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
4
4
0
1
Order By: Relevance
“…Astronium lecointei (Anacardiaceae) and G. glabra (Goupiaceae) are species of the Amazon basin with plenty of research in technological characterisation. The peculiarities found in this study were also reported by Mainieri and Chimelo (1989), Coradin et al (2010), Wheeler (2011) andSantini Junior (2013).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Astronium lecointei (Anacardiaceae) and G. glabra (Goupiaceae) are species of the Amazon basin with plenty of research in technological characterisation. The peculiarities found in this study were also reported by Mainieri and Chimelo (1989), Coradin et al (2010), Wheeler (2011) andSantini Junior (2013).…”
Section: Resultssupporting
confidence: 90%
“…The arrangement, amount of axial parenchyma and the rays storying are anatomical peculiarities that separate this group (Ferreira & Hopkins 2004). Similar characterisations have also been described by Mainieri andChimelo (1989), Ferreira andHopkins (2004), Coradin et al (2010) andSantini Junior (2013).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The state of Mato Grosso has been consolidating itself in both national and international markets as a large producer of wood from native forests, between the years of 2010 and 2014, approximately 32.2 million m³ of in natura, sawed and industrialized/milled wood were commercialized (Cipem, 2014). In a diagnose conducted by Ribeiro (2013), the state has commercialized around 411 species of forest species in a seven year period (2004)(2005)(2006)(2007)(2008)(2009)(2010), showing the biomes great species diversity.…”
Section: Introductionmentioning
confidence: 99%